Performance of a robotic assistance device in computed tomography-guided percutaneous diagnostic and therapeutic procedures - Smakic, Arman; Rathmann, Nils-Andreas; Kostrzewa, Michael; Schönberg, Stefan; Weiß, Christel; Diehl, Steffen J. (CardioVascular and interventional radiology, 2018)
PurposeTo evaluate a commercially available robotic assistance device for computed tomography-guided diagnostic and therapeutic interventions, compared to regular, manually performed CT scan-guided interventions in terms of precision, exposure to radiation to the patient and intervention time.Materials and MethodsOver a period of 6 months, 55 consecutive patients were recruited and treated using robotic assistance and compared to a control group of 101 patients previously treated with a regular CT scan-guided, manual approach. Evaluated parameters were precision (deviation from planned target and number of needle replacements), radiation exposure to the patient and intervention time. Evaluations were performed with regard to complexity (in-plane vs out-of-plane interventions) and type of anesthesia (general vs local).ResultsParameters related to precision were in general significantly better in the robotic assistance group (p < 0.01) with a mean deviation of 1.2 mm (± 1.6 mm) compared to 2.6 mm (± 1.1 mm) in the comparison group. Compared to manual procedure, the mean intervention time was reduced by 15 min (± 5.4 min) on average for an out-of-plane needle placement in the robotic group. There was no increase of exposure to radiation to the patient while radiation exposure for the physician was reduced to zero when the navigation system was used.ConclusionCompared to manual placement, the use of a robotic assistance device in out-of-plane CT-guided interventions under general anesthesia allows for probe placement with high precision. Intervention time is reduced with no increase of exposure to radiation to the patient.